African yam domestication in light of the NGS revolution - (:unkn) unknown (My University, 2019)
Yam (Dioscorea sp.) produces a starchy tuber cultivated for human consumption. It is a backbone for food security in tropical countries, especially in West Africa. The most cultivated species, D. rotundata, originated from Africa. However, due to the lack of archaeological data and genetic tools, very little is known about yam domestication. Currently, the wild progenitor of yam is unclear and the geographical origin of yam cultivation has not been elucidated. Here, we took advantage of the recent sequencing of the D. rotundata genome and the development of new powerful analyses to get new insights into the domestication process of African yam. We analyzed a large sampling of cultivated yam and its two closest wild relatives, the savannah species D. abyssinica and the forest species D. praehensilis, collected in West Africa and Cameroon. Whole genome resequencing produced more than 3 million good quality SNPs and revealed a strong genetic structure between the three species, as well as between Cameroon and West African countries. Using coalescent models, we showed that cultivated yam was domesticated from the forest species D. praehensilis. Spatially explicit models inferred an origin of yam culture expansion in the Niger River basin, in a region located in north Benin.
Keywords: African Research